2014
DOI: 10.3109/10715762.2014.932114
|View full text |Cite
|
Sign up to set email alerts
|

Subsarcolemmal mitochondrial flashes induced by hypochlorite stimulation in cardiac myocytes

Abstract: Mitochondrial superoxide flash (mitoflash) reflects quantal and bursting superoxide production and concurrent membrane depolarization triggered by transient mitochondrial permeability transition in many types of cells, at the level of single mitochondria. Here we investigate reactive oxygen species (ROS)-mediated modulation of mitoflash activity in cardiac myocytes and report a surprising finding that hypochlorite ions potently and preferentially triggered mitoflashes in the subsarcolemmal mitochondria (SSM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Finally, mPTP opening is regulated by a number of signals, such as ROS and Ca 2+ . The roles of oxidants and antioxidants on mitochondrial flash regulation are consistent with mPTP as a trigger, and mitochondrial Ca 2+ uptake indeed enhances mitochondrial flash activity ( 26 , 32 , 41 , 86 ). In plant cells, atractyloside and H 2 O 2 induce mitochondrial flashes.…”
Section: Mitochondrial Flash Activity As a Biomarker Of Mitochondrialmentioning
confidence: 57%
See 1 more Smart Citation
“…Finally, mPTP opening is regulated by a number of signals, such as ROS and Ca 2+ . The roles of oxidants and antioxidants on mitochondrial flash regulation are consistent with mPTP as a trigger, and mitochondrial Ca 2+ uptake indeed enhances mitochondrial flash activity ( 26 , 32 , 41 , 86 ). In plant cells, atractyloside and H 2 O 2 induce mitochondrial flashes.…”
Section: Mitochondrial Flash Activity As a Biomarker Of Mitochondrialmentioning
confidence: 57%
“…Indeed, ischemia drastically suppressed and anoxia abolished, while reperfusion caused a transient increase in flash frequency in intact cardiomyocytes ( 37 , 76 ). Superoxide/ROS signal in flash events detected using mt-cpFYP was confirmed by several groups using various cell types, oxidants, and antioxidants ( 32 , 35 , 37 , 60 , 65 , 86 ). Finally, other superoxide/ROS indicators, including MitoSOX, 2′,7′-dichlorodihydrofluorescein diacetate (DCF) and redox green fluorescent protein (roGFP), have been used to detect increases in superoxide during single mitochondrial flash events ( Table 1 ) ( 5 , 11 , 60 , 79 , 87 ).…”
Section: Discovery and Characterization Of Single Mitochondrial Flashmentioning
confidence: 60%
“…using cpYFP) generated ROS. [56,63,64,67,68]. Recently, Wang et al [56,63,64] and others showed the existence of superoxide flashes in individual mitochondria, using the mitochondrial matrix-targeted superoxide indicator, a circularly permuted yellow fluorescent protein (cpYFP).…”
Section: Discussionmentioning
confidence: 99%
“…Cells displaying healthy contractility were chosen for mitoflash measurement and those near the anode, where electrolysis can produce reactive oxygen species locally (Jackson et al, 1986), were avoided. These cautious measures were necessary because we have recently shown that ROS generated by electrolysis of Tyrode’s solution at the anode can cause significant increase in mitoflash as well as mitochondrial Ca 2+ (Zhang et al, 2014). To minimize interference from cell shortening, image acquisition in contracting cells was at 1 s/frame and synchronized with the electrical pacing, such that it was phase-locked with cell contraction.…”
Section: Methodsmentioning
confidence: 99%